Trends and hot topics in green open space and ecological wisdom research - Manningtyas, Rosyi Damayanti Twinsari; Furuya, Katsunori (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2020)
Studies on green open space and ecological wisdom have developed over time and are linked to various subjects and impacts. However, both research subjects have developed somewhat independently despite their approaches often achieving a sustainable landscape. This paper proposed a bibliometric analysis of green open space and ecological wisdom research to identify the trends and hot topics on both aspects, then determine a potential topic for future research relating to both subject areas. We collected English research papers from the last decades from the Scopus database using appropriate keywords and analyzed the metadata using VOSviewer program. Then, the text data were extracted from the title and abstract of the document collections using VOSviewer built-in text mining function. The hot topic term was analyzed by calculating the score of the average citation based on their occurrences. Finally, potential research in green open space and ecological wisdom field was determined by overlaying the findings and catching the slice. A total of 283 document collections were analyzed and 75 most relevant terms were found. All the terms were divided into four clusters as a research field: urban green space cluster, environmental quality cluster, sustainable planning cluster, and landscape development cluster. Further, the hot topic analysis found ten keywords that had a high citation impact in document collection and mostly came from a sustainable planning cluster. After overlaying the findings, six terms emerged that have a high potential for future research because of their high citation impact for science.